The role of employee empowerment in achieving strategic excellence : exploratory search on a sample of workers in several departments of the Baghdad Mayoralty - Ali Hussein *, Wadhah; M. Al-Amery , Firas. (Journal of Economics and Administrative Sciences, 2024)
This research paper aimed to determine the role of employee empowerment through three dimensions (independence, delegation of powers, and training) in achieving strategic excellence in a number of departments operating in the Baghdad mayoralty, as the employee empowerment strategy is considered one of the strategies of great importance that organizations need at the present time. With the technological and cognitive acceleration witnessed to bring about positive changes in its work, its existence requires organizational components provided by administrative leaders that are able to influence employees and direct them towards achieving success and excellence. The main research problem was represented by the following question: Is it possible to achieve strategic superiority at the level of the Baghdad Municipality through... Empowering employees? The study also aimed to determine the level of empowerment of workers in the departments of the Baghdad Municipality in the research community. To reach the research goal, the researcher relied on the descriptive analytical approach, and a questionnaire tool was used to collect the data required for the research. Statistical programs (SPSS.V.25, Smart Plas4) were also used. To analyze the data, a sample of 100 employees in a number of departments of the Baghdad Municipality was selected. The results of the research concluded that there was a positive effect of empowering employees in achieving strategic excellence. The dimension of delegation of powers had the greatest impact on strategic excellence, followed by the independence dimension and then the training dimension, respectively. The research shed light on the level of variables and the relationship between them in one of the non-profit bodies represented by the Municipality of Baghdad within the Iraqi environment.. Paper type: Research paper